2021
DOI: 10.3390/cancers13225676
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Microenvironment and Efficacy of PD-1 Inhibitors in Relapsed/Refractory Classic Hodgkin Lymphoma: Checkpoint Molecules Landscape and Macrophage Populations

Abstract: To date, the impact of the tumor microenvironment on the prognosis of patients with classic Hodgkin lymphoma (cHL) during anti-PD-1 therapy has been studied insufficiently. This retrospective study included 61 primary samples of lymph nodes from patients who had relapsed/refractory (r/r) cHL and were treated with nivolumab. Repeated samples were obtained in 15 patients at relapse or disease progression after immunotherapy. Median follow-up was 55 (13–63) months. The best overall response rate and progression-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
(100 reference statements)
0
17
0
7
Order By: Relevance
“…Here, we identified a small subset of CD163 + tissue-resident macrophages that drives both primary and secondary resistance against T cell-targeted immunotherapies in preclinical models. These macrophages were highly comparable to a subset of human macrophages with a functional M2 macrophage signature, 27 that is, enriched in human cancers and shares the expression of Maf in the CD163 + macrophage subset recently associated with low response to checkpoint therapy in patients with leukemia 28 as well as the lack of Csf1r expression in the CD163 + macrophage subset associated with resistance to checkpoint therapy in patients with non-small cell lung cancer. 29 While TAM heterogeneity in function and origin is widely acknowledged, macrophages are often grouped on the basis of a few markers.…”
Section: Discussionmentioning
confidence: 77%
“…Here, we identified a small subset of CD163 + tissue-resident macrophages that drives both primary and secondary resistance against T cell-targeted immunotherapies in preclinical models. These macrophages were highly comparable to a subset of human macrophages with a functional M2 macrophage signature, 27 that is, enriched in human cancers and shares the expression of Maf in the CD163 + macrophage subset recently associated with low response to checkpoint therapy in patients with leukemia 28 as well as the lack of Csf1r expression in the CD163 + macrophage subset associated with resistance to checkpoint therapy in patients with non-small cell lung cancer. 29 While TAM heterogeneity in function and origin is widely acknowledged, macrophages are often grouped on the basis of a few markers.…”
Section: Discussionmentioning
confidence: 77%
“…We have observed up‐regulation of LAG‐3 on CD8 + T cells in 48H 3D‐HyGTIC systems after PD‐1 blockade, which was in line with longitudinal paired tumor tissue analysis from Hodgkin Lymphoma patients. [ 43 ] Recently, using SPECT/CT and radiolabeled LAG‐3, Lecocq et al also reported LAG‐3 upregulation after anti‐PD‐1 treatment in MC38 tumor‐bearing mice. [ 44 ] We further confirmed a LAG‐3 up‐regulation trend on CD8 + T cells in NR group of NSCLC patients at Week 8 when compared to the baseline after nivolumab treatment, whereas no dramatic increase in R patients, suggesting that enhanced expression of LAG‐3 might be a strategy adopted by tumor cells to induce the impairment of CD8 + T cells following PD‐1/PD‐L1 axis blocking, [ 32 ] which was further confirmed in the human 3D‐HyGTIC system as well.…”
Section: Discussionmentioning
confidence: 99%
“…c-Maf is essential for macrophage self-renewal but is also expressed in T cells, including Th2 and Th17 cells [27][28][29] . Liu et al identi ed c-Maf as an essential regulator for immunosuppressive macrophage polarization 27 and showed that c-Maf is predominantly expressed in M2-like macrophages in both mice and humans 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PD-L1 expression in cancer cells and surrounding immune cells was not correlated with survival in patients with LAD, suggesting that PD-L1 expression cannot predict outcomes in these patients. Although cancer immunotherapy using anti-PD-L1 immunocheckpoint inhibitors has been widely applied in patients with non-small cell lung cancer, many patients are resistant to such treatment [29][30][31][32][33] . Inhibition of c-Maf may contribute to overcoming such resistance 27 .…”
Section: Discussionmentioning
confidence: 99%